Unveiling the Nexus: Women’s empowerment, climate change and household well-being in Uzbekistan - Alvi, Muzna; Sufian, Farha (CGIAR System Organization, 2025)
Uzbekistan, situated downstream in the Aral Sea Basin, is projected to face severe climate change impacts, including rising temperatures, intensified heat waves, land degradation and increased soil salinization. These changes are expected to exacerbate water and energy scarcity, and environmental challenges, directly threatening agricultural productivity and rural livelihoods, especially for small farmers. In Uzbekistan, small household farms (dekhans), occupy only 13 percent of irrigated arable land, but are the main food producers of the country. Nearly 70 percent of the country’s agriculture produce comes from these small farms, including almost all of the dairy, poultry and livestock. While economically important, small farms have remained outside the purview of government policy and support, and are thus more vulnerable to climate change impacts and system deterioration. Uzbekistan's agrarian reforms have also systematically disadvantaged women, who remain primarily responsible for dehkan farming, with little to no legal recognition of their rights towards the land. Moreover, most energy-related tasks are assigned to women but they have limited control and decision-making power over these resources, especially water resources.